2010
DOI: 10.1007/s12206-010-0406-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buoyancy on soot formation in gas-jet diffusion flame

Abstract: In order to investigate the effect of buoyancy on soot formation in gas-jet diffusion flame, we conducted one set of experiments with the High-Temperature Air Combustion Technology (HiCOT) system and another set under partial gravity conditions. Ethylene (C 2 H 4 ) was used as fuel, and soot volume fractions for the flame were observed as shadow graph images with backlight. In the experiment with the HiCOT, the oxygen concentrations were O 2 = 15 %, 17 %, and 23 %, with constant flame temperature and surroundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A factor of 2-4 increase in peak soot volume fraction was reported from 1 g to l g. Walsh et al [2] found that the laser induced incandescence (LII) signal of a methane coflow laminar diffusion flame increased by a factor of 15 during a parabolic flight. Jeon and Choi [3] studied the buoyancy effect on soot formation in a gas-jet diffusion flame in partial gravity conditions from 0.3 g to 1 g. The soot volume fraction was measured by extinction and found to increase with reduced gravity level. Reimann et al [4] performed LII in a drop tower, measuring both soot concentration and primary particle size.…”
Section: Introductionmentioning
confidence: 99%
“…A factor of 2-4 increase in peak soot volume fraction was reported from 1 g to l g. Walsh et al [2] found that the laser induced incandescence (LII) signal of a methane coflow laminar diffusion flame increased by a factor of 15 during a parabolic flight. Jeon and Choi [3] studied the buoyancy effect on soot formation in a gas-jet diffusion flame in partial gravity conditions from 0.3 g to 1 g. The soot volume fraction was measured by extinction and found to increase with reduced gravity level. Reimann et al [4] performed LII in a drop tower, measuring both soot concentration and primary particle size.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]. The trend of increase in both soot mass and size have been experimentally observed by Walsh et al [7], Jeon and Choi [8], and Reimann et al [9,10] using multiple optical measurement techniques. Experimental observations of non-buoyant round laminar jet diffusion flames were made for various jet flames burning in still air by Diez et al [11] on board the Space Shuttle Columbia to correlate soot volume fraction with estimated mixture fraction for a selection of fuels/pressures.…”
Section: Introductionmentioning
confidence: 59%
“…Among practical combustion schemes for hydrocarbon fuels, along with catalytic and surface burning, the organization of diffusion and pre-mixed reactive gas jets is widespread. In technical applications, reactive diffusion jets are used: in the combustion chambers of heat and power boilers of various power classes; high-temperature technological process of heating, melting, drying and heat treatment of surfaces; associated gas combustion technologies in hydrocarbon fields; multi-flare burners of combustion chambers of condensing boilers of distributed energy [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The diffusion mechanism of flame propagation underlies the formation of forest and man-made fires.…”
Section: Introductionmentioning
confidence: 99%